Input Usage and Productivity in Indian Manufacturing Plants - Ghani, Ejaz; Kerr, William R.; O'Connell, Stephen D. (World Bank, Washington, DC, 2014)
This paper analyzes the scale and productivity consequences of varied input use in Indian manufacturing using detailed plant-level data. Counts of distinct material inputs are higher in urban settings than in rural locations, unconditionally and conditional on plant size, and they are also higher in the organized sector than in the unorganized sector. At the district level, higher input usage in the organized sector is generally observed in wealthier districts and those with greater literacy rates. If looking within states, the usage is more closely associated with electricity access, population density, and closer spatial proximity to one of India's largest cities. Plants in the organized sector utilizing a greater variety of inputs display higher productivity, with the effects mostly concentrated among smaller plants with fewer than 50 employees. For the unorganized sector, there is little correlation of input counts and local conditions, for better or for worse, and a more modest link to productivity outcomes.